The Application of Thematic Progression to Enhance Coherence in Students’ Analytical Exposition Texts - Hariyadi Hariyadi; Sri Wuli Fitriati; Rahayu Puji Haryanti (Universitas Negeri Semarang, 2023)
Thematic progression is the way in which the theme of the clause repeats a meaning from the previous theme or rheme. It also refers to how the information flows in the text. This study aimed to analyze the application of thematic progression to enhance coherence in the analytical exposition texts written by the eleventh graders of SMA Kesatrian 2 Semarang in the academic year 2021/2022. This study used a mixed methods design which was embedded with a case study with the data from the result of students’ texts, observation sheet, and interviews. This study analysed 10 students’ analytical exposition texts. The findings showed that the most type of thematic progression applied was a linear theme reaching 22 times in occurrence, followed by 21 constant theme patterns, and 9 multiple theme patterns. These results showed that a linear theme occurred in the students’ analytical exposition text mostly because it elaborated the writers’ ideas or arguments. Further, thematic progression made the text organize well. This made the texts coherent, and the students’ scores improved from pre-test with mean of 74.50 to post-test with mean of 89.00. Then, the value of significance (2-tailed) was 0.000 which meant that the improvement was statistically significant. These results are expected to give a contribution to other researchers in conducting research in various text types. Furthermore, the results are useful for students to improve their writing and for teachers to improve the way they teach writing.